Supporting community management: a synthesis of successful rural water services programmes in India - Hutchings, Paul (Cranfield University, 2016)
For the past 30 years the dominant approach to managing rural water services in low and lower middle income countries has been the community management approach. Yet there is increasing evidence the model is not fit for purpose as too many services fail. The next generation ideas for community management emphasise the need for continuous on-going support to communities – an approach known as the community management plus approach. This thesis tests and develops this next generation community management plus paradigm. It analyses field data from twenty case studies of ‘reportedly successful’ community management programmes across seventeen states in India. Bringing together data from 2,355 household surveys, 272 interviews and 130 focus groups it provides a synthesis that assesses the type and level of support found in successful examples of community management. The evidence from these case studies demonstrates that communities receive significant recurrent subsidy covering between 7-48% of operational expenditure. This is in marked contrast to the conventional principles of community management whereby communities cover 100% of these costs. Analysis of organisation types also shows how community management has been shaped by the devolution of governance in rural India. Many community management programmes involve a structural overlap between the local self- government institution of the Gram Panchayat and water committees. The thesis argues this represents a shift to the ‘institutionalised co-production’ of rural water services, involving both the state and private citizens in public service delivery. Overall, the research shows that successful community management in India involves continuous on-going support as per the community management plus paradigm. However this has required the nesting of the model within the broader system of local self-government which blurs the lines between public and community management.
Keywords: Rural water; Services; Community; Management; India; Finance; Subsidy; Maintenance; Participation; Public; Political; Economy; Governance